Psychological distress in newly diagnosed colorectal cancer patients following microsatellite instability testing for Lynch syndrome on the pathologist’s initiative - Landsbergen, K. M. (Springer Netherlands, 2012)
According to the Dutch Guideline on Hereditary Colorectal Cancer published in 2008, patients with recently diagnosed colorectal cancer (CRC) should undergo microsatellite instability (MSI) testing by a pathologist immediately after tumour resection if they are younger than 50 years, or if a second CRC has been diagnosed before the age of 70 years, owing to the high risk of Lynch syndrome (MIPA). The aim of the present MIPAPS study was to investigate general distress and cancer-specific distress following MSI testing. From March 2007 to September 2009, 400 patients who had been tested for MSI after newly diagnosed CRC were recruited from 30 Dutch hospitals. Levels of general distress (SCL-90) and cancer-specific distress (IES) were assessed immediately after MSI result disclosure (T1) and 6 months later (T2). Response rates were 23/77 (30%) in the MSI-positive patients and 58/323 (18%) in the MSI-negative patients. Levels of general distress and cancer-specific distress were moderate. In the MSI-positive group, 27% of the patients had high general distress at T1 versus 18% at T2 (p = 0.5), whereas in the MSI-negative group, these percentage were 14 and 18% (p = 0.6), respectively. At T1 and T2, cancer-specific distress rates in the MSI-positive group and MSI-negative group were 39 versus 27% (p = 0.3) and 38 versus 36% (p = 1.0), respectively. High levels of general distress were correlated with female gender, low social support and high perceived cancer risk. Moderate levels of distress were observed after MSI testing, similar to those found in other patients diagnosed with CRC. Immediately after result disclosure, high cancer-specific distress was observed in 40% of the MSI-positive patients.